THE STUDY ON QUANTITATIVE ASSESSMENT OF STORM SURGE COMPONENTS BY NUMERICAL MODEL - Dang, Vu Hai; Thuy, Nguyen Ba; Chien, Do Dinh; Kim, Sooyoul (Vietnam Journal of Marine Science and Technology, 2017)
In this study, components of storm surge caused by wind, atmospheric pressure and wave are calculated and analyzed by using integrated numerical models of tides, waves and storm surge (SuWAT - Surge, Wave and Tide). The influence of tide is also considered. In which, tide and storm surge are calculated based on two-dimensional nonlinear shallow water equations considering surge component generated by wave radiation stress that is calculated from the SWAN model, a component model in SuWAT model. The model is applied to calculate storm surge during Xangsane typhoon in Da Nang in September 2006 with a number of different computing cases. The results show that influence of tide is negligible due to small tidal amplitude, surge caused by atmospheric pressure is only significant in offshore areas where storm intensity is still strong. Meanwhile, surge components caused by wind stress and wave radiation stress dominate total water level in coastal areas